Property aspects of intellectual property - Rognstad, Ole-Andreas (Cambridge, United Kingdom : Cambridge University Press, 2018)
For many years, there have been discussions about whether intellectual property (IP) is really property. The property concept, particularly when used in transnational and international concepts, remains somewhat elusive. Here, Ole-Andreas Rognstad comprehensively discusses the use of the property metaphor in relation to IP in a transnational perspective. Rognstad gives an overview of main aspects of the IP/property interface, notably the justification and the structuring of the rights and intellectual property rights as assets. Moreover, he highlights the importance of distinguishing between these aspects, even though they are closely linked to each other. The book takes a transnational approach, dealing with recent developments in European human/fundamental rights law and international investment law, helping readers to understand the practical implications of the IP/property interface.
Property in justifying rights -- Property in the structuring of rights -- Property as assets -- Conclusions to be drawn from the justification of rights -- Conclusions to be drawn from structure of rights -- Conclusion to be drawn from IPRs as assets -- Final conclusions.
Includes bibliographical references (pages 202-218) and index.
Keywords: Intellectual property; Property